Lysine auxotrophy combined with deletion of the SecA2 gene results in a safe and highly immunogenic candidate live attenuated vaccine for tuberculosis. - Joseph Hinchey; Bo Y Jeon; Holly Alley; Bing Chen; Michael Goldberg; Steven Derrick; Sheldon Morris; William R Jacobs; Steven A Porcelli; Sunhee Lee (PLoS ONE)
Tuberculosis (TB) caused by Mycobacterium tuberculosis remains a major global health problem, despite the widespread use of the M. bovis Bacille Calmette-Guerin (BCG) vaccine and the availability of drug therapies. In recent years, the high incidence of coinfection of M. tuberculosis and HIV, as well as escalating problems associated with drug resistance, has raised ominous concerns with regard to TB control. Vaccination with BCG has not proven highly effective in controlling TB, and also has been associated with increasing concerns about the potential for the vaccine to cause disseminated mycobacterial infection in HIV infected hosts. Thus, the development of an efficacious and safe TB vaccine is generally viewed as a critical to achieving control of the ongoing global TB pandemic. In the current study, we have analyzed the vaccine efficacy of an attenuated M. tuberculosis strain that combines a mutation that enhances T cell priming (ΔsecA2) with a strongly attenuating lysine auxotrophy mutation (ΔlysA). The ΔsecA2 mutant was previously shown to be defective in the inhibition of apoptosis and markedly increased priming of antigen-specific CD8(+) T cells in vivo. Similarly, the ΔsecA2ΔlysA strain retained enhanced apoptosis and augmented CD8(+) T cell stimulatory effects, but with a noticeably improved safety profile in immunosuppressed mice. Thus, the M. tuberculosis ΔsecA2ΔlysA mutant represents a live attenuated TB vaccine strain with the potential to deliver increased protection and safety compared to standard BCG vaccination.